P11.68.A Hemangiopericytoma, case series and clinic-pathological analysis. (5th September 2022) - Redaelli, V; Calatozzolo, C; Marucci, G; Pinzi, V; Gaviani, P; Botturi, A; Simonetti, G; Mattei, L; Pollo, B; Silvani, A
Abstract: Background: Hemangiopericytoma (HPC) is an extremely rare aggressive tumor of mesenchymal origin, which constitutes less than 1% of primary tumors of the central nervous system. Typically it occurs in young adults (mean age at diagnosis 30-50 years). Initially described as gemmangiomas, was first called hemangiopericytoma in 1942 but it was considered as a variant of meningioma until 1993 when it was finally recognized as a distinct clinical-pathological entity by the World Health Organization (WHO). In 2016, there was the unification of both HPC and Solitary Fibrous Tumor (SFT) in a single spectrum of rare and thick mesenchymal tumors due to the identification, in both tumoral types, of a molecular alteration called NAB2-STAT6 fusion. Material and Methods: The present study is a case series of patients that received a pathological diagnosis of SFT/HPC at our Institute from 1981 to 2020. Clinical data included: demographic data, tumor characteristics and treatment modality. Hystological diagnosis and immunohistochemistry allowed to confirm diagnosis, based on the 2016 WHO classification. Haematoxylin staining was completed with immunohistochemistry with primary antibodies for STAT 6 and evaluation of presence of tumor necrosis. Statistical analysis was conducted considering age at first diagnosis, treatment modality, extent of tumor resection, presence of necrosis in histological analysis compared to PFS-1, OS and relapses number. Results: The case series was composed by 82 patients (46 men and 36 women) with median age of 43 (± 20) that accede to our Institute from 1981 to 2020. Our statistical analysis showed significative correlation between age, extend of tumor resection and presence of necrosis with OS and relapses number. Conclusion: Hemangiopericytoma is a very rare cerebral tumors, and for this reason large case series are not disposable in literature. In our study we collected all disposable data of every patient with pathological diagnosis of SFT/HPC acceded to our hospital in the long period of 39 years in the aim to verify the presence of significative correlations. We observed strong correlation between tumor resection and presence of necrosis in tumor tissue with prognosis parameters (OS and number of relapses). This result it could be important to conduct the decisional process about treatment after surgical resection, considering also pathological features, rather than only surgical resection.